Multiple Exemplar Instruction: Systematic Review of Experimental Studies (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
We carried out a systematic review of experimental studies that investigated the effects of Multiple Exemplar Instruction (MEI) on the induction of ‘bidirectional naming’ (BiN) and ‘interdependence between verbal repertoires’ (IVR). The databases Wiley, PUBMED, SciELO, Web of Science and Scopus were searched using the term 'multiple exemplar', resulting in a final selection of 24 studies (12 of which used MEI to induce BiN and 12 to promote IRV). We reviewed participant profiles, methods employed for training and for testing, and results. In general, it was observed that: (1) participants were mainly children with atypical development; (2) most studies used Identity Matching to Sample + Tact (IDMTS+tact) for training and for pre-and post-tests of repertoires trained with MEI; testing was done mainly for mands, pure tacts and ‘speaker unidirectional naming’; (3) The testing methods used most often for BiN were alternating trials of IDMTS + tacts, listener repertoire, and pure and impure tacts (for BiN), and alternating trials of mand and pure tact (for IRV); (4) In general, studies showed evidence of the induction of IRV and ‘speaker unidirectional naming’. However, we argue that the studies lacked adequate tests of ‘joint bidirectional naming’ and ‘incidental bidirectional naming’. Research is suggested to overcome this limitation and advance knowledge about IRV.
Keywords: multiple exemplar instruction; bidirectional naming; interdependence between verbal repertoires